2011
DOI: 10.1063/1.3597608
|View full text |Cite
|
Sign up to set email alerts
|

Collisions of ageostrophic modons and formation of new types of coherent structures in rotating shallow water model

Abstract: International audienceWe study collisions of recently discovered ageostrophic modons in rotating shallow water model at different values of impact parameter and find that two new types of coherent vortex structures may be formed during this process: "nonlinear" modons, i.e., coherent dipoles with essentially nonlinear scatter plot and coherent tripoles. Both are known for incompressible 2D Euler equations, but were not reported in the "compressible" shallow water model. Inelastic scattering with strong filamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…To test the robustness of the shock modons, we performed a number of simulations of their collisions, similar to our previous study [9]. They show that shock modons undergo frontal collisions forming either a new pair of shock modons after partner exchange, or a ''shock tripole'' with a fusion of anticylonic vortices.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…To test the robustness of the shock modons, we performed a number of simulations of their collisions, similar to our previous study [9]. They show that shock modons undergo frontal collisions forming either a new pair of shock modons after partner exchange, or a ''shock tripole'' with a fusion of anticylonic vortices.…”
mentioning
confidence: 91%
“…Such ''shock modon'' appears as a result of relaxation of the QG modon with large Ro. As in our previous papers on ageostrophic modons [8], [9] we work with a newgeneration finite-volume code for RSW equations, which is well balanced (i.e., preserves equilibrium solutions) and entropy satisfying (i.e. guarantees the energy decrease across shocks) [10].…”
mentioning
confidence: 99%
“…The results presented above on the scattering of quasi-barotropic modons are not very different from what occurs in the barotropic one-layer model (Lahaye & Zeitlin 2011, 2012, which is due to the almost barotropic character of ageostrophic modons. The main difference is the trapped waves which appear in the baroclinic component in the two-layer case.…”
Section: Frontal Scattering Of Baroclinic Modonsmentioning
confidence: 67%
“…In previous studies with a one-layer model it was found that the AGMs survive frontal collision, forming two AGMs after exchange of partners (Ribstein et al 2010). Afterwards, we found that other collisions may produce new types of multipoles in the RSW model: the tripole (T) and the nonlinear ageostrophic modon (NAGM) (Lahaye & Zeitlin 2011). The former consists of an anticyclonic core with two cyclonic satellites, while the latter is a dipole with a reduced global Rossby number, because of larger distance between the two vorticity cores, and essentially nonlinear scatter plot of B versus PV (cf.…”
Section: Preliminary Discussion Of the Adjustment Experimentsmentioning
confidence: 98%
“…Such scatter plots are standard in diagnosing coherent structures of any nature in rotating shallow water models, cf. [23][24][25] and references therein. The structure in question is coherent if the points of the plot form a curve, as compared to a dispersed cloud in the opposite case.…”
Section: B Nonlinear Saturation Of the Instabilitymentioning
confidence: 99%